Ectopic varices (2008)
The term 'ectopic varices' defines the varices formed secondarily to portal hypertension occurring anywhere in the abdomen except in the cardioesophageal region. Bleeding from these varices is unusual and difficult to diagnose. The prognosis may be poor with high morbidity and mortality. Management of this condition has been adapted from experience with esophagogastric varices. Due to its low frequency no randomized trials of therapeutic modalities are available. © Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.